FOULING BEHAVIOR OF MODIFIED CELLULOSE ACETATE ASYMMETRIC MEMBRANES FOR DIFFERENT BRACKISH WATER TREATMENT - Tutuk Djoko Kusworo; B Budiyono; Eva Sofiana; Ulfah Nurul Aulia Rochyani; Dani Puji Utomo (Reaktor, 2017)
Water treatment technology which is being widely developed is membrane technology as an alternative technology with sieving mechanism principle.The main purposes of this research are to investigate the effects of additives and thermal treatment on the cellulose acetate membrane morphology and performance in treating brackish water.The membrane was fabricated by preparation of dope solution consits of cellulose acetate and acetone. The membrane was casted via NIPS method using mechanic casting knife. Dope solution was prepared by varying the PEG concentration of 1 and 5wt-% and the annealing temperature at 60°C and 25°C for 10 seconds. The backwash technique was used to solve fouling mechanism in this system .The results of SEM and FTIR showed that theb higher PEG addition to the dope solution resulted in larger membrane pore size and increase the hydrophilic properties of membrane. However the higher temperature and the longer annealing timg, the skin layer of membrane become denser. The result was also shown that back wash technique can reduced fouling phenomenon in the membrane.